The Effect of Consumer Perceived Trust and Image Toward Food Brands on Consumers’ Willingness to Buy - Abdalrahman, Mohammed; Lehota, József (Táplálkozásmarketing, 2019)
Purpose – consumers’ buying process is affected by many variables in which branding strategy is indeed an important variable to be considered. This paper aims to evaluate the influence of three branding elements – brand name, packaging, and country of origin – on Palestinian consumers’ willingness to buy food products to understand better their buying. Methodology – The study was conducted in the Palestinian market, the sample was selected according to simple random sampling technique, and a structured questionnaire was prepared, then it was electronically distributed by using emails and social media. The questionnaire contains 35 questions depending on a balanced Fifth Likert Scale and a single-item 7-point differential semantic scale, the questions intended to determine the influence of the selected branding elements on consumers’ willingness to buy food products. The data were analysed depending on the descriptive analysis and one sample t-test. Findings – according to the results of the data analysis it was found that product features and attributes were the factors of the highest importance that influenced the consumers’ willingness to buy, while the branding elements variables came at second rank of importance. Also, the results show that the effect of three chosen branding elements on consumer willingness to buy is significant. The outcomes of this study may be advantageous for firms working in food sectors, since the Palestinian market is lacking such a scientific study and help them in creating marketing strategies to increase the sales volume of their products.JEL Codes: M31, M39